2013
DOI: 10.1074/jbc.m113.485953
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Pattern of Protein Glycosylation Modulates the Thermostability of a GH11 Xylanase

Abstract: Background: The molecular basis of increased protein stability by N-glycosylation is incompletely understood. Results: Glycosylation position rather than number is more important for protein thermostability in the xylanase A from Bacillus subtilis. Conclusion: Glycans contribute both to stabilizing protein-glycan and less favorable glycan-glycan interactions. An extensive protein-glycan interface favors protein stability. Significance: Formation of a protein-glycan interface provides a conceptual framework to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 45 publications
(49 reference statements)
3
39
0
3
Order By: Relevance
“…From our results, Asn-37 is involved in a more homogenous glycosylation and plays a more critical role in enzymatic activity and thermostability. These findings suggest that the glycosylation site modification causes various effects, similar to the previous observation (Fonseca-Maldonado et al 2013). Interestingly, both glycosylation sites are located near to the S/T surface that is supposed to play a role in protein stability of GH11 xylanases.…”
Section: Discussionsupporting
confidence: 74%
“…From our results, Asn-37 is involved in a more homogenous glycosylation and plays a more critical role in enzymatic activity and thermostability. These findings suggest that the glycosylation site modification causes various effects, similar to the previous observation (Fonseca-Maldonado et al 2013). Interestingly, both glycosylation sites are located near to the S/T surface that is supposed to play a role in protein stability of GH11 xylanases.…”
Section: Discussionsupporting
confidence: 74%
“…While the partial glycosylation slightly affects the thermostability of NfPG5, the huge glycosylation has a marked effect on the thermostability of NfPG4. Dispersed glycosylation sites are suggested to favor stabilizing protein-glycan interactions [32]. Through molecular modeling, we observed that the eight glycosylation sites are dispersed on the protein surface of NfPG4 (data not shown).…”
Section: Effects Of Glycosylation On Enzyme Propertiesmentioning
confidence: 90%
“…Glycosylation is well-known to affect various aspects of enzyme properties [32]. Although the molecular mechanism is poorly understood, the covalently attached glycans can stabilize a protein, increase the resistance of a protein against proteinase degradation, regulate the activity of an enzyme, and help protein folding [32,33].…”
Section: Effects Of Glycosylation On Enzyme Propertiesmentioning
confidence: 99%
“…Of the over 25 distinct PTMs that have been experimentally identified, phosphorylation, acetylation, and N-linked glycosylation are the most frequent, and extensive databases allow for routine access to statistics and properties of PTMs 118,-110 . It is possible to introduce or remove PTMs into proteins through the modulation of sequence motifs (e.g.…”
Section: Modulating Protein Stabilitymentioning
confidence: 99%
“…In an example of the use of MD in this area, Fonseca-Maldonaldo and Ward investigated the relationship between the pattern of glycosylation and xylanase thermostability by systematically modulating the pattern of glycosylation 118 (Figure 3D). GH11 xylanase from Bacillus subtilis has 6 putative glycosylation sites (N8, N20, N25, N29, N141 and N181) and in WT, 4 sites were glycosylated (N20, N25, N141 and N181) when expressed in Pichia pastoris 118 .…”
Section: Modulating Protein Stabilitymentioning
confidence: 99%